STRATEGI ADAPTASI MASYARAKAT DESA HUTAN RAWA GAMBUT PASCA KEBAKARAN HUTAN DAN LAHAN DI KALIMANTAN SELATAN - Hafizianor Hafizianor; Gt.Syeransyah Rudi (Jurnal Hutan Tropis, 2021)
The fire of forest and land especially in forest swamp forest have cause changes in the environment biophysical significant the impact on the occurrence of changes in the environment social. Changes in the environment biophysical and environmental social as the impact of the change over to the area of forest swamp peat has been encouraging people to do the adaptation so that they still exist as individuals and as a community to sustain life ( existence ) and improved its well-being life ( welfare ). Based on the background behind it then needs to do research. From the results of the interim research, it was found that there were various adaptation patterns of the community in adapting to peat swamp forest after fires, including adaptation of land use and adaptation of job diversification outside of work based on forest and peat swamp land use.